Islamic Counseling in the Perspective of Digital Ethics and Muslim Family Responsibility - Firdaus, Adkhau Fajar Nurzakiy; Maziza, Arina; Hidayatulloh, Anang; Nisa’, Finidia Choirun (Proceedings Of International Conference On Islamic Counseling Studies (ICONICS), 2025)
The development of digital technology has changed various aspects of life, including in the practice of counseling. In Indonesia, high internet access has led to the birth of online counseling services, but this has also raised new challenges related to ethics, privacy, and communication effectiveness. Islamic counseling is present as an approach that integrates psychological and spiritual aspects based on the Qur’an and Hadith, so as to be able to answer the needs of modern society without losing religious values. This study uses a descriptive qualitative method through a literature study to analyze Islamic counseling from the perspective of digital ethics and the role of Muslim families in building moral resilience in the era of technological disruption. The results of the study show that Islamic counseling in the digital era will be more effective if Islamic values are combined with digital ethics, supported by Islamic digital literacy, and strengthened by the active role of Muslim families.